2013
DOI: 10.1111/j.1476-5381.2012.02226.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo pharmacological interactions between a type II positive allosteric modulator of α7 nicotinic ACh receptors and nicotinic agonists in a murine tonic pain model

Abstract: BACKGROUND AND PURPOSEThe a7 nicotinic ACh receptor subtype is abundantly expressed in the CNS and in the periphery. Recent evidence suggests that a7 nicotinic ACh receptor (nAChR) subtypes, which can be activated by an endogenous cholinergic tone comprising ACh and the a7 agonist choline, play an important role in chronic pain and inflammation. In this study, we evaluated whether type II a7 positive allosteric modulator PNU-120596 induces antinociception on its own and in combination with choline in the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 60 publications
(88 reference statements)
1
47
3
Order By: Relevance
“…The decreased locomotor activity could be related to the microdialysis results showing that PAM-2 potentiates nicotine-induced neurotransmitter (i.e., glutamate, dopamine, and serotonin) levels in the rat striatum (Arias, 2013), a brain area involved in the coordination of body movements. On the contrary, PNU-120596 (type II PAM) did not change the observed nicotine-induced locomotor activity in mice (Freitas et al, 2013c), although these experiments were performed with a higher dose of nicotine (0.5 mg/kg) than that in our experiments (0.2 mg/kg).…”
Section: Discussioncontrasting
confidence: 48%
“…The decreased locomotor activity could be related to the microdialysis results showing that PAM-2 potentiates nicotine-induced neurotransmitter (i.e., glutamate, dopamine, and serotonin) levels in the rat striatum (Arias, 2013), a brain area involved in the coordination of body movements. On the contrary, PNU-120596 (type II PAM) did not change the observed nicotine-induced locomotor activity in mice (Freitas et al, 2013c), although these experiments were performed with a higher dose of nicotine (0.5 mg/kg) than that in our experiments (0.2 mg/kg).…”
Section: Discussioncontrasting
confidence: 48%
“…For instance, PNU-120596 induced analgesic activity by its own or combined with choline in the formalin pain test, and showed anti-allodynic effects in the CCI neuropathic pain model [33][34][35]. On the other hand, it is reported that different dietary polyphenols, like chlorogenic acid (CGA), resveratrol and quercetin derivatives, have antinociceptive effects on acute, inflammatory and neuropathic pain models [36][37][38], although their mechanisms of action are not totally understood.…”
Section: Analgesic Activitymentioning
confidence: 96%
“…For instance the α7 nAChR PAM PNU-120596 caused a significant reduction in mechanical hyperalgesia in rats [182]. Additionally, PNU-120596 is able to decrease formalin-induced pain by itself, and in combination with the α7 nAChR agonists choline, nicotine and PHA-543613 [183]. PNU-120596 is also able to reduce edema induced by a hind paw infusion of carrageenan in mice [184].…”
Section: Painmentioning
confidence: 99%